2016
DOI: 10.37757/mr2016.v18.n3.9
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in Screening and Diagnosis of Gestational Diabetes: Cuba’s Position

Abstract: médico con doble especialidad en endocrinología y en medicina familiar y maestría en salud integral de la mujer. Profesor auxiliar e investigador adjunto,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The main known risk factors were: age > 35 years (50%), family history of diabetes in a first or second-degree relative (50%), history of GDM (16%) and ethnic characteristic (black, and hispanic) (20). Several studies demonstrated the role of maternal age as a risk factor within the framework of GDM screening (7,8,21). The mean age in our study was indeed similar to reports from France and worldwide (13,14).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The main known risk factors were: age > 35 years (50%), family history of diabetes in a first or second-degree relative (50%), history of GDM (16%) and ethnic characteristic (black, and hispanic) (20). Several studies demonstrated the role of maternal age as a risk factor within the framework of GDM screening (7,8,21). The mean age in our study was indeed similar to reports from France and worldwide (13,14).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, in French Guiana, the prevalence of macrosomia (2.6%), corrected for age and sex, was low, despite frequent social precariousness (42). In Cuba, Cruz et al found macrosomia rates of 10% to 20% (7). This difference between our study and the prevalence of macrosomia in neighboring countries or in South America, where precariousness is also frequent, is probably linked with the routine hospital admission of high-risk pregnancies in French Guiana during the last 2 months and/or weekly follow-up in multidisciplinary consultations for patients with easy mobility.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations